Influence of crystal growth conditions and carbothermal treatment on activator charge state in Ti:sapphire - Nizhankovskiy, S.V.; Sidelnikova, N.S.; Baranov, V.V. (Functional Materials, 2018)
Presented are the results of comparative studies of the influence of carbothermal treatment of the raw material (Al₂O₃ and TiO₂ powders) and reducing properties of the growth medium on the charge state of titanium ions in Al₂O₃:Ti crystals. It is shown that carbothermal treatment at temperatures of 1700-1800°C makes it possible to additionally decrease the relative content of titanium in the charge state Ti⁴⁺ by 2.5-3 times.